Identification of Factors Determining Winning in Men's and Women's Beach Volleyball: a Logistical Regression Approach - Gopal Kumar; Anshuman Shukla; Amit Chhoker; Rohit Kumar Thapa (OVS LLC, 2021)
The purpose of this study was to find the factors responsible for winning in the men's and women's beach volleyball championship. Materials and methods. The study sample consisted of a total of 212 matches for men and 214 matches for women of the 2017 & 2019 FIVB Men and Women Beach Volleyball World Championships held at Vienna & Hamburg from 28 July to 6 Aug 2017 and 28 June to 7 July 2019. The matches were played by 192 teams (both men and women combined) consisting of 384 numbers (both men and women combined) of players from different nations. The data were analyzed using Binary Logistic Regression (Forward: LR Method) with the result of the game as the dependent variable and predictor variables as covariates. β, standard error β, Wald's χ2, odds ratio with 95% confidence interval were calculated. Model evaluation was conducted using the likelihood ratio test, Cox & Snell (R2), and Nagelkerke (R2) tests. The goodness of fit test for the models was conducted using the Hosmer & Lemeshow test. Results. The analysis revealed seven factors related to winning in men's and women's competition. While in league rounds, six factors in men's and seven factors in women's competition were related to winning. Besides, in knockout rounds, four factors in men's and six factors in women's competition were related to winning. Conclusion. The study shows that there is a significant association of important factors with respect to winning a match in an elite beach volleyball championship. The coaches and players can take note of the important factors responsible for winning in the elite beach volleyball championship, with different factors playing an important role in men's and women's competition during league and knockout rounds as well.